2010
DOI: 10.1524/zkri.2010.1353
|View full text |Cite
|
Sign up to set email alerts
|

MIL-53(Fe): a good example to illustrate the power of powder diffraction in the field of MOFs

Abstract: Abstract. The field of "Metal-Organic Frameworks" (MOFs) has grown exponentially, giving rise to nanoporous materials with promising applications in gas storage, molecular separation or catalysis. Despite the use of solvothermal synthesis, some MOFs can be obtained only as polycrystalline samples and in those cases, powder diffraction is essential to characterize them. Herein, the nanoporous iron(III) terephthalate MIL-53(Fe), has been chosen to illustrate the power of powder diffraction in the field of MOFs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…This distance is close to that previously observed in the largest filled tunnel in the (INT) form and much larger than the one seen in MIL-53(Fe)[H 2 O] (Fe-Fe = 7.643 Å) as expected taking into account the kinetic diameter of both different guest molecules. 23 In this (NP) form, the CO 2 molecules are closely aligned with the long diagonal of the rhombic cross section of the channels and stacked along the c-axis in such a way that they are (i) almost parallel to each other and (ii) nearly perpendicular to the inorganic chains. This stacking seen in the (NP) form is in closed agreement with the one found from ab initio molecular dynamics simulations for MIL-53(Sc)-int, even if only half the pores were filled by CO 2 in that case.…”
Section: Co 2 Localization By X-ray Powder Diffractionmentioning
confidence: 99%
“…This distance is close to that previously observed in the largest filled tunnel in the (INT) form and much larger than the one seen in MIL-53(Fe)[H 2 O] (Fe-Fe = 7.643 Å) as expected taking into account the kinetic diameter of both different guest molecules. 23 In this (NP) form, the CO 2 molecules are closely aligned with the long diagonal of the rhombic cross section of the channels and stacked along the c-axis in such a way that they are (i) almost parallel to each other and (ii) nearly perpendicular to the inorganic chains. This stacking seen in the (NP) form is in closed agreement with the one found from ab initio molecular dynamics simulations for MIL-53(Sc)-int, even if only half the pores were filled by CO 2 in that case.…”
Section: Co 2 Localization By X-ray Powder Diffractionmentioning
confidence: 99%
“…And the peaks at 284.8 and 288.3 eV represent the benzoic acid ring and C═O in the H 2 BDC ligand, respectively . In the N 1s spectra of Figure C, two peaks appear at 400.1 and 398.6 eV, which are attributed to the C═N in the triazine unit and C─N in the connecting unit, respectively . The O 1s spectra are shown in Figure D.…”
Section: Resultsmentioning
confidence: 95%
“…MIL‐53(Fe) shows little change in unit cell volume upon dehydration and heating: in fact upon removal water the structure contracts slightly, although essentially remains in the closed‐pore form, Figure a . For this iron analogue the synthetic chemistry allows a partially fluorinated form to be prepared where the bridging hydroxides are fractionally replaced by fluoride anions, but both materials show the same lack of pore‐opening and the only difference between them is a small change in crystal symmetry . There is no definitive explanation for the different behaviour of MIL‐53(Fe) compared to MIL‐53(Cr), but it has been speculated that shorter inter‐ring distances between the linkers in the iron form of the material imply stronger π‐π interactions that prevent the framework from opening upon heating, even once water is desorbed …”
Section: The Crystal Chemistry Of Mil‐53mentioning
confidence: 99%
“…prepared the aluminium form of MIL‐53 containing crystals of a few hundred microns in dimension using HF as a mineraliser, borrowing from the synthetic chemistry used in zeolite crystallisation . But the majority of structural studies of MIL‐53 materials rely on powder diffraction methods, often using the high resolution offered by synchrotron X‐ray sources to refine atomic‐scale structural detail . It is interesting to note that in situ diffraction studies of the crystallisation of MIL‐53 have shown that a structurally unrelated material MOF‐235 can form at short reaction times, and thus synthesis must be carefully planned to obtain the desired product.…”
Section: Introductionmentioning
confidence: 99%